On the Relationship Between Mixe-zoquean and Uto-aztecan - Wichmann, Soren (Kansas Working Papers in Linguistics, 1999)
The paper seeks to establish evidence for the relationship between UtoAztecan and Mixe-Zoquean, a relationship which was proposed by Whorf (1935), but never before substantiated by actual comparisons. In order to reduce the factor of chance resemblances proto-forms are compared. Given the several thousand years of nonproximity of the two language families, borrowing cannot be used as an explanation for the similarities in vocabulary. In several instances the comparisons reveal regular correspondences involving non-idental segments, correspondences of a sort that is expected in true genetic relationships.